Pkm Kelompok Nelayan Pengolah Ikan Pari Asap - Harlina, Harlina; Hadijah, Sitti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
Stingray is a fish that is non-economical and less delicious when it is consumed fresh, but when it is processedby fogging, then the taste will be very delicious and popular among the community.So the smoked stingray is one of thetypical and popular products in Jeneponty regency. The processing of smoked stingrays in Jeneponto Regency is locatedin ToreangSubdistrict, namely "Pari Jaya" Business Group and in Arungkeke Sub-district the group named "PariIndah" Business Group. These two groups are partners in thiscommunity servicesprogram. The biggest problem faced bythe community is the amount of production is still meager.This is because, in the smoked process, it only uses the smokefrom the kitchen stove with an open system so that fumigation is not running perfectlyand it resultsthe quality of stingraysmoke is still very low and not hygienic.Moreover,it is directly marketed without packaging, and cash flow is managingwell. Through this community servicesprogram, partners are provided with training and assistance in the application ofclosed-loop fogging technology. So that the smoked stingrays produced will be durable, safe, nutritious and hygienic. Inaddition, partners are built in the diversification of processed products of smoked stingrays, packaging techniques so thepackaging is attractive. It is expected to have competitive power in the marketbe able to apply business management well.The results of this activity can generallybe concluded that stingray curing technique by using closed system can beaccepted by the partner group because the process of smoked stingray is more quickly mature, the procedure is easier andmore hygienic. The packaging of smoked stingray products is more interesting and more durable